FEATURES OF THE COURSE OF METASTASES FROM MERKEL CELLS - А. С. Ходак; В. П. Ходак (Український радіологічний та онкологічний журнал, 2020)
Summary. Carcinoma of the skin from Merkel cells is characterized by an aggressive course and a high incidence of relapses and metastases. Due to the rare occurrence, diagnostic errors and inadequate treatment are often tolerated. Among the priority tasks are early diagnosis of Merkel’s carcinoma, correct prognostic evaluation and adequate individual treatment of patients.